Analisa Yuridis Penerapan Good Corporate Governance Pada Usaha Asuransi Mutual (Studi Terhadap Asuransi Jiwa Bersama Bumiputera 1912) - Alvizt Vega desra (Jurnal Ilmu Hukum, 2022)
This study aims to identify and analyses the regulation and implementation of Good Corporate Governance or good corporate governance for mutual insurance companies in Indonesia. And to find out what the responsibilities of the statutory manager appointed by the OJK that are to restructure AJB Bumiputera towards the application of good corporate governance principles. This research was conducted using a normative juridical approach because it uses library materials as the main material, namely primary legal materials consisting of basic norms or rules, provisions of laws and regulations relating to the principles of Good Corporate Governance, especially in insurance companies. The results show that the application of the principles of Good Corporate Governance at AJB Bumiputera has been carried out in accordance with the company's articles of association, but it is still not optimal and adequate due to the absence of regulations that specifically regulate the Mutual Insurance Business in Indonesia. The statutory manager's responsibility for implementing the principles of good corporate governance has been carried out with maximum efforts, although it has not been in line with expectations. Because until now, AJB Bumiputera has not been able to make payment of claims that are due to policyholders, which is a violation of the principles of fairness.